PREPARATION OF ACTIVATED CARBON FROM PALM SHELL BY CHEMICAL ACTIVATION WITH KOH AS AN ADSORBENT DYE - Lestari, Intan -; Apriansyah, Rendi; Gusti, Diah Riski; Naswir, M.; Permana, Edwin (Department of Chemistry, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2024)
Activated carbon is a well known as porous material, with large specific surface area, which is useful in adsorption of both gases and solutes from aqueous solution. In this research, prepraration of activated carbon was through chemical activation of palm shells using KOH as an activator. Preparation of carbon from palm shell were the first carbonized in a furnace at temperature of 400 - 500 °C. Carbon is soaked in KOH activator solution for 8 hours and then carbonized at a temperature of 600 - 800 °C. The activated carbon obtained was characterized by XRD, SEM and FTIR. Characterization using SEM shows that activated carbon has pores and using FTIR shows the presence of several functional groups such as hydroxyl (-OH), carboxyl (-COOH), carbonyl (-C=O) that can be used for adsorption. Adsorption studies were carried out using batch experiments with synthetic naphthol and remazole dye solutions. The adsorption study was carried out in batch, based on isotherm assumptions and following Langmuir isotherm model. These results indicate that palm shell activated carbon has the potential used as an adsorbent for removing naphthol and remazole dyes from the solution.